Nation Building in the Context of 'One Zambia One Nation' - Kashoki, Mubanga E. (Project Muse, 2018)
In this collection of essays the author discusses questions of definition and explores the complex issues of national integration, identity, language, belonging, and national unity. Professor Kashoki argues that 'One Zambia One Nation' is much more than a political slogan.